Evaluating ex vivo toll-like receptor agonist response as a potential biomarker in equine gastric ulcer syndrome - Gustavo Ferlini Agne; Daniel Thomas Barratt; Bridget Eileen May; Mark R. Hutchinson; Joshua Holmes; Catherine Steel; Olivier Simon; Samuel Greig Evans; Andrew A. Somogyi; Benjamin W. Sykes; Samantha Franklin (The Veterinary Journal, 2026)

Conditioned comfort: A multi-scalar analysis of residential heat adaptation in the tropical city-state of Singapore - Sarah Hian May Chan; Joshua Dao-Wei Sim; Natalia Borzino; Yunjing Li; Khant Min Naing; Pearl Min Sze Tan; Yi Xuan Tay; Flora Yuting Du; Samuel Chong Wei Chng; Jason Kai Wei Lee; Kai Zheng; Harvey Neo (Urban Climate, 2026)

Private cooling, urban heat, and the limits of collective climate action in tropical cities - Natalia Borzino; Samuel Chng; Sarah Hian May Chan; Khant Min Naing; Yi Xuan Tay; Harvey Neo (Sustainable Cities and Society, 2026)

Molecular relatedness-based analyses reveal breeding site philopatry in female bluntnose sixgill sharks (Hexanchus griseus) - Shawn Larson; Dayv Lowry; Kelly Andrews; Claude Dykstra; Francis Juanes; Brian Timmer; Samuel May (Frontiers in Marine Science, 2026)
The bluntnose sixgill shark ( Hexanchus griseus ) is a deep-water, globally distributed, but data-limited species due to its habitat use and cryptic nature. Its slow growth, long lifespan, and uncertain population status have prompted concern about its vulnerability and resulted in an IUCN Red List status of “Near Threatened.” A lack of information about critical habitat use throughout the species’ life cycle, such as breeding grounds, complicates direct management of the species. This study investigates the genetic diversity, population structure, relatedness, and reproductive behaviors of sixgill sharks in the Salish Sea, an inland fjord encompassing Washington State, USA and British Columbia Canada, one of the few known pupping and rearing grounds of the species globally. Using genomic sequencing of 274 tissue samples opportunistically collected over a 16-year timespan, we found no evidence of spatial or temporal genetic population structure within the Salish Sea and moderate levels of neutral genetic diversity. Multiple paternity in two litters confirmed polyandrous mating, a strategy that may enhance genetic diversity. Relatedness analyses revealed philopatry, with close relatives identified across disparate years, demonstrating that mature females or their relatives return to this nursery ground over time for pupping. These findings provide new insights into the life history of the sixgill shark and emphasize the critical role of nursery habitats, such as the Salish Sea, in their reproductive success, underscoring the need for targeted conservation efforts to protect these sharks and their known critical habitats.

The threat of multidrug-resistant microorganisms: active surveillance of key antimicrobial resistant pathogens in 2025 - a report from the INVIFAR network - Adrián Martínez-Meléndez; Elvira Garza-González; María del Rosario Vázquez-Larios; Melissa Garibaldi-Rojas; Bernardo Alfonso Martinez-Guerra; Christian Daniel Mireles-Davalos; Samuel Pavel Escalante-Armenta; José Manuel Feliciano-Guzmán; Daniel Romero-Romero; Maria del Consuelo Velazquez-Acosta; Sandra Quintana-Ponce; Shaúl Ariel Navarro-Lara; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2026)
Purpose Systematic collection and analysis of antimicrobial resistance data from key bacterial pathogens is essential to contribute to control antimicrobial resistance (AMR). The aim of this work was to survey the drug resistance on clinically relevant organisms stratified according to age, gender, clinical specimens and facilities. Methods Microbiological data were collected from 55 centers across 24 states in Mexico between January 1 and March 31, 2025. Bacterial identification and antimicrobial susceptibility testing were performed at each participating center using locally available methods. Data was processed using WHONET 2025. Isolates obtained from lower respiratory specimens, urine, blood, biopsies and abscesses were analyzed. Carbapenem non-susceptible isolates were further analyzed by PCR for common carbapenemase-encoding genes. Resistance frequencies were compared using the chi-square test. Results A total of 11,290 clinical isolates were analyzed, mostly from urine ( n = 7,149; 63.3%), followed by blood ( n = 1,370; 12.1%). The most prevalent was Escherichia coli ( n = 6,185; 54.8%), followed by Klebsiella pneumoniae ( n = 1,365; 12.1%) and Pseudomonas aeruginosa ( n = 1,110; 9.8%). Resistance to carbapenems in E. coli was higher in respiratory isolates (imipenem: 5.8%, p = 0.016; meropenem: 5.3%, p < 0.001), with 75.9% producing extended-spectrum ß-lactamases (ESBLs). K. pneumoniae had the highest resistance to ampicillin/sulbactam (52.5%, p = 0.028) and sulfamethoxazole/trimethoprim (62.1%, p = 0.014) in blood isolates, and 63.2% were ESBL-producers ( p = 0.001). In P. aeruginosa , urine isolates showed significantly higher resistance to ceftolozane-tazobactam (24.7%, p = 0.008), ceftazidime-avibactam (36.6%, p < 0.001), and meropenem (34.5%, p = 0.009) compared to other clinical specimens included. For A. baumannii , respiratory isolates had 73.6% resistance to meropenem ( p < 0.001). S. aureus from blood showed 25.7% resistance to oxacillin ( p < 0.004). The most frequent carbapenemase genes were bla OXA−48−like in E. coli (26/56, 46.4%), bla NDM for K. pneumoniae (7/17, 41.2%), bla OXA−24 in A. baumannii (79/108, 73.1%) and bla IMP for P. aeruginosa (18/108, 16.7%). Conclusion This surveillance study underscores the elevated levels of antimicrobial resistance, ESBL production, and carbapenemase activity among priority pathogens, including some Enterobacterales , P. aeruginosa , and A. baumannii . These findings emphasize the urgent need to strengthen epidemiologic surveillance programs in Mexican healthcare settings.

Improving genomic selection and diversity with cryopreservation: A case study in Atlantic salmon - Emmanuel A. Lozada-Soto; Mark P. Polinski; Harvey D. Blackburn; Brian C. Peterson; Samuel A. May (Aquaculture, 2026)

The Genomics Revolution in Nonmodel Species: Predictions vs. Reality for Salmonids - Samuel A. May; Samuel W. Rosenbaum; Devon E. Pearse; Marty Kardos; Craig R. Primmer; Diana S. Baetscher; Robin S. Waples (Molecular Ecology, 2025)
The increasing feasibility of whole‐genome sequencing has been highly anticipated, promising to transform our understanding of the biology of nonmodel species. Notably, dramatic cost reductions beginning around 2007 with the advent of high‐throughput sequencing inspired publications heralding the ‘genomics revolution’, with predictions about its future impacts. Although such predictions served as useful guideposts, value is added when statements are evaluated with the benefit of hindsight. Here, we review 10 key predictions made early in the genomics revolution, highlighting those realised while identifying challenges limiting others. We focus on predictions concerning applied aspects of genomics and examples involving salmonid species which, due to their socioeconomic and ecological significance, have been frontrunners in applications of genomics in nonmodel species. Predicted outcomes included enhanced analytical power, deeper insights into the genetic basis of phenotype and fitness variation, disease management and breeding program advancements. Although many predictions have materialised, several expectations remain unmet due to technological, analytical and knowledge barriers. Additionally, largely unforeseen advancements, including the identification and management applicability of large‐effect loci, close‐kin mark–recapture, environmental DNA and gene editing have added under‐anticipated value. Finally, emerging innovations in artificial intelligence and bioinformatics offer promising new directions. This retrospective evaluation of the impacts of the genomic revolution offers insights into the future of genomics for nonmodel species.

Using eDNA to Supplement Population Genetic Analyses for Cryptic Marine Species: Identifying Population Boundaries for Alaska Harbour Porpoises - Kim M. Parsons; Samuel A. May; Zachary Gold; Marilyn Dahlheim; Christine Gabriele; Janice M. Straley; John R. Moran; Kimberly Goetz; Alexandre N. Zerbini; Linda Park; Phillip A. Morin (Molecular Ecology, 2025)
Isolation by distance and biogeographical boundaries define patterns of population genetic structure for harbour porpoise along the Pacific coast from California to British Columbia. Until recently, inadequate sample sizes in many regions constrained efforts to characterise population genetic structure throughout the coastal waters of Alaska. Here, tissue samples from beachcast strandings and fisheries bycatch were supplemented with targeted environmental DNA (eDNA) samples in key regions of Alaska coastal and inland waters. Using a geographically explicit, hierarchical approach, we examined the genetic structure of Alaska harbour porpoises, using both mitochondrial DNA (mtDNA) sequence data and multilocus SNP genotypes. Despite a lack of evidence of genetic differentiation from nuclear SNP loci, patterns of relatedness and genetic differentiation from mtDNA suggest natal philopatry at multiple geographic scales, with limited gene flow among sites possibly mediated by male dispersal. A priori clustering of sampled areas at an intermediate scale (eastern and western Bering Sea, Gulf of Alaska and Southeast Alaska) best explained the genetic variance (12.37%) among regions. In addition, mtDNA differentiation between the Gulf of Alaska and eastern Bering Sea, and among regions within the Gulf of Alaska, indicated significant genetic structuring of harbour porpoise populations in Southeast Alaska. The targeted collection of eDNA samples from strata within Southeast Alaska was key for elevating the statistical power of our mtDNA dataset, and findings indicate limited dispersal between neighbouring strata within coastal and inland waters. These results provide evidence supporting a population boundary within the currently recognised Southeast Alaska Stock. Together, these findings will prove useful for ongoing management efforts to reduce fisheries conflict and conserve genetic diversity in this iconic coastal species.

Tidal gradients, fine‐scale homing and a potential cryptic ecotype of wild spawning pink salmon ( Oncorhynchus gorbuscha ) - Samuel A. May; Kyle R. Shedd; Peter S. Rand; Peter A. H. Westley (Molecular Ecology, 2023)
The homing behaviour of salmon is a remarkable natural phenomenon, critical for shaping the ecology and evolution of populations yet the spatial scale at which it occurs is poorly understood. This study investigated the spatial scale and mechanisms driving homing as depicted by spawning site‐choice behaviour in pink salmon ( Oncorhynchus gorbuscha ) in Prince William Sound, Alaska. Molecular pedigree analyses of over 30,000 adult spawners in four streams revealed that pink salmon exhibit fine‐scale site fidelity within a stream, returning to within